A highly spatially resolved GIS-based model to assess the isoprenoid emissions from key Italian ecosystems - Pacheco, Claudia Kemper; Fares, Silvano; Ciccioli, Paolo (Atmospheric Environment, 2014)
The amount of Biogenic Volatile Organic Compounds (BVOC) emitted from terrestrial vegetation is of great importance in atmospheric reactivity, particularly for ozone-forming reactions and as condensation nuclei in aerosol formation and growth. This work presents a detailed inventory of isoprenoid emissions from vegetation in Italy using an original approach which combines state of the art models to estimate the species-specific isoprenoid emissions and a Geographic Information System (GIS) where emissions are spatially represented. Isoprenoid species and basal emission factors were obtained by combining results from laboratory experiments with those published in literature. For the first time, our investigation was not only restricted to isoprene and total monoterpenes, but our goal was to provide maps of isoprene and individual monoterpenes at a high-spatial (∼1 km2) and temporal resolution (daily runs, monthly trends in emissions are discussed in the text). Another novelty in our research was the inclusion of the effects of phenology on plant emissions. Our results show that: a) isoprene, a-pinene, sabinene and b-pinene are the most important compounds emitted from vegetation in Italy; b) annual biogenic isoprene and monoterpene fluxes for the year 2006 were ∼31.30 Gg and ∼37.70 Gg, respectively; and c) Q. pubescens+Q. petrea+Q. robur, Q. ilex, Q. suber and Fagus sylvatica are the principal isoprenoid emitting species in the country. The high spatial and temporal resolution, combined with the species-specific emission output, makes the model particularly suitable for assessing local budgets, and for modelling photochemical pollution in Italy.
Keywords: BVOC inventory; isoprene; Isoprenoids; Italian forests; Monoterpenes

Intra- and inter-annual variability of VOC emissions from natural and semi-natural vegetation in Europe and neighbouring countries - Steinbrecher, Rainer; Smiatek, Gerhard; Köble, Renate; Seufert, Günther; Theloke, Jochen; Hauff, Karin; Ciccioli, Paolo; Vautard, Robert; Curci, Gabriele (Atmospheric Environment, 2009)
Biogenic VOC emission estimates from the earth’s surface are crucial input parameters in air quality models. Knowledge accumulated in the last years about BVOC source distributions and chemical compound species emission proﬁles in Europe as well as the demand of air quality modellers for a ﬁner resolution in space and time of BVOC estimates have led to the set-up of new emission modelling systems. An updated fast BVOC emission modelling platform explicitly considering the seasonality of emission potentials and leaf temperature gradients in forest canopies by the semi-empirical emission module (seBVOC) will be proposed and used for estimating hourly values of chemical compound-speciﬁc emissions in Europe (33–68 north; 10 west to 40 east) in the years 1997, 2000, 2001, and 2003. Spatial resolution will be 10 km by 10 km. The database used contains latest land and forest distributions, updated foliar biomass densities, leaf area indices (LAI), and plant as well as chemical compound-speciﬁc emission potentials, if available. Meteorological input parameters for the respective years will be generated using the non-hydrostatic meteorological model MM5. Highest BVOC emissions occur in daytime hours around noon from the end of May to mid-August in the Mediterranean area and from the mid of June to the end of July in the boreal forests. Comparison of 3 BVOC model approaches will reveal that for July 2003, the European isoprene and monoterpene totals range from 1124 Gg to 1446 Gg and from 338 Gg to 1112 Gg, respectively. Small-scale deviations may be as high as 0.6 Mg km2 for July 2003, reﬂecting the current uncertainty range for BVOC estimates. Key sources of errors in inventories are still insufﬁciently detailed land use data for some areas and lacking chemically speciated plantspeciﬁc emission potentials in particular in boreal, south-eastern, and northern African landscapes. The hourly emissions of isoprene, speciated terpenes, and oxyVOC have been made available by the NatAir database.
Keywords: BVOC; Emission modelling; Inventory; Isoprenoids; oxyVOC; Sequiterpenes

Intra- and inter-annual variability of VOC emissions from natural and semi-natural vegetation in Europe and neighbouring countries - Steinbrecher, Rainer; Smiatek, Gerhard; Köble, Renate; Seufert, Günther; Theloke, Jochen; Hauff, Karin; Ciccioli, Paolo; Vautard, Robert; Curci, Gabriele (Atmospheric Environment, 2009)
Biogenic VOC emission estimates from the earth’s surface are crucial input parameters in air quality models. Knowledge accumulated in the last years about BVOC source distributions and chemical compound species emission proﬁles in Europe as well as the demand of air quality modellers for a ﬁner resolution in space and time of BVOC estimates have led to the set-up of new emission modelling systems. An updated fast BVOC emission modelling platform explicitly considering the seasonality of emission potentials and leaf temperature gradients in forest canopies by the semi-empirical emission module (seBVOC) will be proposed and used for estimating hourly values of chemical compound-speciﬁc emissions in Europe (33–68 north; 10 west to 40 east) in the years 1997, 2000, 2001, and 2003. Spatial resolution will be 10 km by 10 km. The database used contains latest land and forest distributions, updated foliar biomass densities, leaf area indices (LAI), and plant as well as chemical compound-speciﬁc emission potentials, if available. Meteorological input parameters for the respective years will be generated using the non-hydrostatic meteorological model MM5. Highest BVOC emissions occur in daytime hours around noon from the end of May to mid-August in the Mediterranean area and from the mid of June to the end of July in the boreal forests. Comparison of 3 BVOC model approaches will reveal that for July 2003, the European isoprene and monoterpene totals range from 1124 Gg to 1446 Gg and from 338 Gg to 1112 Gg, respectively. Small-scale deviations may be as high as 0.6 Mg km2 for July 2003, reﬂecting the current uncertainty range for BVOC estimates. Key sources of errors in inventories are still insufﬁciently detailed land use data for some areas and lacking chemically speciated plantspeciﬁc emission potentials in particular in boreal, south-eastern, and northern African landscapes. The hourly emissions of isoprene, speciated terpenes, and oxyVOC have been made available by the NatAir database.
Keywords: BVOC; Emission modelling; Inventory; Isoprenoids; oxyVOC; Sequiterpenes

Modeling volatile isoprenoid emissions – a story with split ends - Grote, R; Niinemets, Ü (Plant Biology, 2008)
Accurate prediction of plant-generated volatile isoprenoid fluxes is necessary for reliable estimation of atmospheric ozone and aerosol formation potentials. In recent years, significant progress has been made in understanding the environmental and physiological controls on isoprenoid emission and in scaling these emissions to canopy and landscape levels. We summarize recent developments and compare different approaches for simulating volatile isoprenoid emission and scaling up to whole forest canopies with complex architecture. We show that the current developments in modeling volatile isoprenoid emissions are “split-ended” with simultaneous but separated efforts in fine-tuning the empirical emission algorithms and in constructing process-based models. In modeling volatile isoprenoid emissions, simplified leaf-level emission algorithms (Guenther algorithms) are highly successful, particularly after scaling these models up to whole regions, where the influences of different ecosystem types, ontogenetic stages, and variations in environmental conditions on emission rates and dynamics partly cancel out. However, recent experimental evidence indicates important environmental effects yet unconsidered and emphasize, the importance of a highly dynamic plant acclimation in space and time. This suggests that current parameterizations are unlikely to hold in a globally changing and dynamic environment. Therefore, long-term predictions using empirical algorithms are not necessarily reliable. We show that process-based models have large potential to capture the influence of changing environmental conditions, in particular if the leaf models are linked with physiologically based whole-plant models. This combination is also promising in considering the possible feedback impacts of emissions on plant physiological status such as mitigation of thermal and oxidative stresses by volatile isoprenoids. It might be further worth while to incorporate main features of these approaches in regional empirically-based emission estimations thereby merging the “split ends”.
Keywords: BVOC emission; Isoprenoids; Modeling; Scaling; Spatial variability; temporal variability

Light and temperature dependence of the emission of cyclic and acyclic monoterpenes from holm oak (Quercus ilex L.) leaves - Staudt, M; Bertin, N (Plant, Cell & Environment, 1998)
In a laboratory study, we investigated the monoterpene emissions from Quercus ilex, an evergreen sclerophyllous Mediterranean oak species whose emissions are light dependent. We examined the light and temperature responses of individual monoterpenes emitted from leaves under various conditions, the effect of heat stress on emissions, and the emission-onset during leaf development. Emission rate increased 10-fold during leaf growth, with slight changes in the composition. At 30 °C and saturating light, the monoterpene emission rate from mature leaves averaged 4·1 nmol m–2 s–1, of which α-pinene, sabinene and β-pinene accounted for 85%. The light dependence of emission was similar for all monoterpenes: it resembled the light saturation curve of CO2 assimilation, although monoterpene emission continued in the dark. Temperature dependence differed among emitted compounds: most of them exhibited an exponential increase up to 35 °C, a maximum at 42 °C, and a slight decline at higher temperatures. However, the two acyclic isomers cis-β-ocimene and trans-β-ocimene were hardly detected below 35 °C, but their emission rates increased above this temperature as the emission rates of other compounds fell, so that total emission of monoterpenes exponentially increased from 5 to 45 °C. The ratio between ocimene isomers and other compounds increased with both absolute temperature and time of heat exposure. The light dependence of emission was insensitive to the temperature at which it was measured, and vice versa the temperature dependence was insensitive to the light regime. The results demonstrated that none of the models currently applied to simulate isoprene or monoterpene emissions correctly predicts the short-term effects of light and temperature on Q. ilex emissions. The percentage of fixed carbon lost immediately as monoterpenes ranged between 0·1 and 6·0% depending on temperature, but rose up to 20% when leaves were continuously exposed to temperatures between 40 and 45 °C.
Keywords: biogenic VOC emission; emission model; heat stress; Holm oak; Isoprenoids; light effect; Monoterpenes; Quercus ilex; temperature effect